2006
DOI: 10.1016/j.physd.2006.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Super-spreaders and the rate of transmission of the SARS virus

Abstract: We describe a stochastic small-world network model of transmission of the SARS virus. Unlike the standard Susceptible-Infected-Removed models of disease transmission, our model exhibits both geographically localised outbreaks and "super-spreaders". Moreover, the combination of localised and long range links allows for more accurate modelling of partial isolation and various public health policies. From this model, we derive an expression for the probability of a widespread outbreak and a condition to ensure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 19 publications
1
86
0
1
Order By: Relevance
“…The model included as agents those who were infected but not yet infectious, and as the main result the authors found that outbreaks could be prevented if the patients with symptoms were isolated as soon as possible. Another model applied to SARS spreading of virus in Hong Kong can be found in [405]. In 2007, Small et al [406] studied the distribution of avian influenza virus among wild and domestic birds and obtained a network with scale-free topology with no epidemic threshold.…”
Section: Epidemic Spreadingmentioning
confidence: 99%
“…The model included as agents those who were infected but not yet infectious, and as the main result the authors found that outbreaks could be prevented if the patients with symptoms were isolated as soon as possible. Another model applied to SARS spreading of virus in Hong Kong can be found in [405]. In 2007, Small et al [406] studied the distribution of avian influenza virus among wild and domestic birds and obtained a network with scale-free topology with no epidemic threshold.…”
Section: Epidemic Spreadingmentioning
confidence: 99%
“…The obtained results on heterogenous networks are based on the hypothesis that the larger the degree of an infected individual, the greater the capability for infection it has, i.e., hub=super −spreader [13] . However, in [6][7][8], Zhou, et al argued that this hypothesis is not always true.…”
Section: Nonlinear Infectivitymentioning
confidence: 99%
“…Recently, the study on dynamical behaviors of complex networks has become a focus of great interest in this research field, such as the synchronization and the pinning control of dynamical networks, the epidemic of disease [4][5][6][7][8][9][10][11][12][13][14][15][16], etc. Especially, there are attempts to control the dynamics of a complex network and drive the network to an desired state.…”
Section: Introductionmentioning
confidence: 99%